Killed on Blueberry Hill - Farrow, Sharon (Farrow, Sharon. Berry Basket mystery., 2018)
The Blueberry Blow Out festival has begun and it<U+2019>s time for Marlee Jacob, owner of The Berry Basket, to shine. Unfortunately it<U+2019>s also bringing out the worst in her fiancé Ryan Zeller. Ryan<U+2019>s rivalry with Porter Gale, owner of Blueberry Hill Farm, spills over into a very public and very ugly fight. And after they compete in the pie-eating contest and a raucous tug of war, their orchard blood feud takes a deadly turn . . . The death of the king of Blueberry Hill is a shock but not too surprising<U+2014>he was a diabetic whose last pig out meal was deliciously fatal. But when authorities discover that someone tampered with Porter<U+2019>s insulin, a tragic accident is looking like murder<U+2014>and Ryan is the key ingredient. Now Marlee<U+2019>s investigation to clear his name is taking her deep into the Gale family secrets, and she<U+2019>s being shadowed every step of the way by a killer whose sweet revenge is just beginning . . .